The Problems of Teaching Computer Material Concerning Fourth Grade Students’ Point of View of in the Department of Computer College of Education for Women / University of Baghdad (Journal Of Educational and Psychological Researches, 2022)
The aim of the research is to identify the problems of teaching computer material concerning fourth grade students’ point of view in the computer department in the College of Education for Women by identifying the statistically significant differences between the answers of female students to problems in the field of school administration and in the field of teaching computer subject included the sample of research On (39) of (50) students and (78%) From the fourth grade students in the department of computer who had achieved the theoretical part in the first semester and the assembly application in the second semester in the schools of Baghdad city for the academic year (2018-2019). In order to verify the two objectives of the research; a closed questionnaire was set . It consisted of (37) paragraphs addressing the problems of teaching the subject of Computer science. Then (17) paragraphs reflecting problems related to the field of administration. And (20) paragraphs reflecting problems in the field of teaching the subject on the triangular scale (yes, no, I don't know). The questionnaire is presented to a group of experts specialized in the field of teaching methods, measurement, evaluation and computer to determine its suitability for application, The stability of the resolution determined using half-hash method where it reached (0.60) which is a good stability factor, the resolution was applied to the fourth graders in the department of computer immediately after the end of the period of the assembly application to identify the most important problems encountered during that period in Baghdad City Schools. After the use of repetitions and percentages and square Kai it was recognized that the most important problems suffered by computer teachers in the Baghdad City Schools and according to the importance are: lack of internet and Assisting books in school, lack of weekly hours to teach the subject, lack of computer books, The belief that computer material is secondary material in the school, the lack of sufficient computers in the school laboratory In the field of teaching the subject, the most important problems are the lack of the net in the teaching of the subject, the lack of training students on the use of computer skills, lack of interest in field visits related to the computer ,the use of traditional teaching method A set of recommendations and proposals related to the current research field are concluded...